PENERAPAN METODE PEMBELAJARAN BRAINSTORMING DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN BAHASA INDONESIA PADA SISWA KELAS V SDN 164319 TEBING TINGGI - Rismawaty Tampubolon (Universitas Negeri Medan, 2020)
The aim of this research is to improve learning result on Indonesian Language subject through brainstorming method. This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from grade V, SD Negeri 164319 Tebing Tinggi which amounted to 33 students. This study used a qualitative descriptive analysis technique. The results showed that the method of the brainstorming in Indonesian Language subject can improve student learning result characterized by increased mastery learning students, namely pre-cycle (69,7%), the first cycle (81,8%), cycle II (90,9 %) and complete learn the clasical equal to 90,9 %.Keywords: Brainstorming, Indonesian Language